RESPON KINERJA PRODUKSI DAN FISOLOGIS KAMBING PERANAKAN ETTAWA TERHADAP PEMBERIAN PAKAN TAMBAHAN DEDAK HALUS PADA AGROEKOSISTEM LAHAN KERING di KALIMANTAN SELATAN - Akhmad - Hamdan; B. P. Purwanto; D. A. Astuti; A. Atabany; E. Taufik (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2018)
ABSTRACTPerformance and Physiological Response Peranakan Ettawa Goat to Supplementary Feeding With Rice Bran on Dryland Agroecosystem in South Kalimantan. This research was to know the performance of Peranakan Ettawa goat and physiological responses tosupplementation feeding of rice bran in the area of dryland agroecosystem in South Kalimantan. This design of experiment was a 4 x 4 Latin Square using 4 Etawa goats of second lactation with average of body weight of 47.50 ± 3.32kg/doe. There were 4 levels of rice bran supplementation ie P1 (0%), P2 (30%), P3 (50%) and P4 (70%) of dry matter requirement. The main feed was a mixture of rambanan (Niponan (Clibadium surinamense L), Rawatan (Pachystilidium hirsutum (Blume), Laban (Vitex pinnata L), Kacangan (Centrosema pubescens B) dan Dadap alas (Mallotus paniculatus). Drinking water was provided ad libitum. Parameters observed were feed intake, milk production and physiological response (heart rate, respiration, rectal temperature and skin temperature). The data obtained were analyzed using the procedure of